ANALISIS PENGARUH CAPITAL ADQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFOMING LOAN (NPL) DAN SIZE TERHADAP NET INTEREST MARGIN (NIM) ( Pada Bank Umum Yang Telah Go Publik di Bursa Efek Indonesia Periode 2012 - 2016 ) - Ika Wahyu Indra Sari, 14.05.52.0123; Taswan, Taswan (Students' Journal of Accounting and Banking, 2018)
The purpose of this study was to examine the influence of Capital Adquacy Ratio, Loan to Deposit Ratio, Non Perfoming Loan, and Size of Net Interest Margin on Bank’s go public in Indonesian Stock Exchane year 2012-2016.This research was conducted using secondary data. The population in this study are all Bank’s listed in Indonesia Stock Exchane year 2012-2016. The Sample in this study using puposive sampling method. The analytical method used in this research is multiple regression analysis. The research proves that, CAR positive and not significant effect on Net Interest Margin, LDR positive and significan effect on Net Interest Margin, NPL positive and not significan effect on Net Interest Margin, and Size negative and not significant on Net Interest Margin. Adjusted R Square Volue is 0,132 this means that 13,2 of the dependet variable can be explaned by other causes outside the model. Keyword : Net Interest Margin, Capital Adquacy Ratio, Loan to Deposit Ratio, Non Perfoming Loan, and Size